PERBANDINGAN SUMBER DAYA HONEYPOT BERBASIS COWRIE DAN OPENCANARY TERHADAP SERANGAN SSH BRUTE-FORCE DAN PORT-SCANNING - Yoga Pramana; Raphael Bianco Huwae; Andy Hidayat Jatmika (Program Studi Teknik Informatika, Fakultas Teknik, Universitas Mataram, 2026)
The rapid advancement of information technology demands good security. One approach that can be taken and is considered effective for identifying and analyzing cyberattacks is to implement a honeypot security layer. In a comparative study of two types of honeypots, namely Opencanary and Cowrie, which examined the form of honeypot response and the main focus of resource requirements to attacks along with the use of two methods of brute-force and port-scanning attacks. The attack was carried out virtually with the self-attack method, with the aim of comparing each honeypot in terms of resource requirements. The results show that in brute-force attacks, Opencanary has lower resource requirements with the highest CPU/RAM requirements of only 14% / 1.3%, while Cowrie requires more resources with the highest CPU/RAM requirements of 17% / 1.3%. While port-scanning attacks have lower resource requirements with the highest CPU requirements in Opencanary at 3% and Cowrie at 2% and similar RAM requirements at 1.28%. This study is expected to be a benchmark in selecting a honeypot that is tailored to the existing resource requirements.